Advancing hydrogen: a closer look at implementation factors, current status and future potential - Kaheel, Sultan; Ibrahim, Khalifa Aliyu; Fallatah, Gasem; Lakshminarayanan, Venkatasubramanian; Luk, Patrick Chi-Kwong; Luo, Zhenhua (MDPI, 2023)
This review article provides a comprehensive analysis of the hydrogen landscape, outlining the imperative for enhanced hydrogen production, implementation, and utilisation. It places the question of how to accelerate hydrogen adoption within the broader context of sustainable energy transitions and international commitments to reduce carbon emissions. It discusses influencing factors and policies for best practices in hydrogen energy application. Through an in-depth exploration of key factors affecting hydrogen implementation, this study provides insights into the complex interplay of both technical and logistical factors. It also discusses the challenges of planning, constructing infrastructure, and overcoming geographical constraints in the transition to hydrogen-based energy systems. The drive to achieve net-zero carbon emissions is contingent on accelerating clean hydrogen development, with blue and green hydrogen poised to complement traditional fuels. Public–private partnerships are emerging as catalysts for the commercialisation of hydrogen and fuel-cell technologies, fostering hydrogen demonstration projects worldwide. The anticipated integration of clean hydrogen into various sectors in the coming years signifies its importance as a complementary energy source, although specific applications across industries remain undefined. The paper provides a good reference on the gradual integration of hydrogen into the energy landscape, marking a significant step forward toward a cleaner, greener future.
Keywords: sustainable clean energy; renewable energy development; carbon emissions reduction; global energy transition; international energy policies; decarbonisation strategies; hydrogen policy framework